If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 5 = 1x + -5 Reorder the terms: 5 + -3x = 1x + -5 Reorder the terms: 5 + -3x = -5 + 1x Solving 5 + -3x = -5 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5 + -3x + -1x = -5 + 1x + -1x Combine like terms: -3x + -1x = -4x 5 + -4x = -5 + 1x + -1x Combine like terms: 1x + -1x = 0 5 + -4x = -5 + 0 5 + -4x = -5 Add '-5' to each side of the equation. 5 + -5 + -4x = -5 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = -5 + -5 -4x = -5 + -5 Combine like terms: -5 + -5 = -10 -4x = -10 Divide each side by '-4'. x = 2.5 Simplifying x = 2.5
| y^4-13y^3=42y^2 | | 6=.5+2 | | 2m-3+m=15 | | 24n(n-1)=0 | | x^2-17x+84=0 | | 3x^2-x-6=0 | | -12x-4(5+10x)=11(-3x+12) | | 9x=5x+9x-15 | | c(c-17)=0 | | 3x+6=2x+9 | | 4=-0.8 | | 5x+5=5x+x+2 | | 10x+6=6x-8+10x-16 | | 12*11-20= | | 16x-9=5x+12x-20 | | 10x+9-11-x=-2(2x+4)-3(2x-2) | | 5*1+2*(3-1)=6 | | n-14n-6=-5 | | n-14n-6=-6 | | 4x+3=5x+4x-3 | | 5=2x+5x-2 | | 5*5-(25/5)=20 | | 5*5-(25/5)= | | 4=4x-2+2x | | 75=3(6x-5) | | 9x-9=3x+6+x+6 | | 5x+45+-89=90+41 | | a^3-16ab^2=0 | | 5x+45-89=90+41 | | 4(5-6)+6x=6 | | -0.5x-7=-11 | | a(2x+3)=ax+12 |